Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Karyawan BMT NU Kabupaten Pamekasan - Nufus, Yuhyin; Basalamah, Muhammad Ridwan; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine and analyze the influence of organizational culture and work motivation on employee performance at BMT NU Pamekasan Regency. Employee performance can be interpreted as an assessment tool that compares the abilities and skills of employee work results or that have been completed. This study is an explanatory research study with a quantitative approach. This study collected data with a total of 60 respondents who were employees of BMT NU Pamekasan Regency. The variables contained in this study are organizational culture, work motivation, and employee performance. The results of this study indicate that organizational culture and work motivation have a significant effect on employee performance, organizational culture has a significant effect on employee performance, and work motivation has a significant effect on employee performance. This study suggests that companies continue to maintain and improve employee consistency by providing job promotions, appreciation, and benefits, as well as improving more communicative services. Keywords: Organizational Culture, Work Motivation, and Employee Performance